G438(P) Comparing the well–being and mental health of looked after children (lac). (27th April 2015) - Lee, AM; Simkiss, D; Keegan, J
Abstract : Introduction: Evidence suggests that Looked after children are nearly 5 times more likely to have a mental illness than their peers. Over the last decade the concept of well-being has developed, especially within public policy. There is a hypothesis that improving an individuals well-being improves their mental health and reduces any associated mental illness. Aims: To assess the relationship between well-being and mental health problems in looked after children. Methods: From January 2014, the Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) was added to the Strengths and Difficulties Questionnaire (SDQ) completed by all Looked After Children in Birmingham aged 14 years old and above. In August 2014, we retrieved data on all children with completed SDQ and WEMWBS scores. Results: 101 children were identified as having a completed WEMWBS and SDQ score. 32 of the children's SDQ scores were >17 reflecting the child having substantial risk of clinically significant mental health problems. 64 of the children with completed WEMWBS scored average scores of 40–59, 14 children scored below average, and the remaining 23 children scored above average. Figure 1 shows the WEMWBS and SDQ scores. 4 children scored 55 (an average score) on the WEMWBS and their SDQ scores ranged from 8–35 (from low to high risk of clinically significant mental health problems). Conclusion: There is no clear relationship between mental health problems and well-being scores for Looked After Childern in this cohort. This finding supports the statement in the Chief Medical Officer Annual Report 2013 that 'mental illness and 'well-being' are not ends of the same continuum: it is possible to have high levels of subjective well-being despite having a mental illness, and vice versa'.